2012
DOI: 10.1371/journal.pone.0037241
|View full text |Cite
|
Sign up to set email alerts
|

A Cohort Study of Serum Bilirubin Levels and Incident Non-Alcoholic Fatty Liver Disease in Middle Aged Korean Workers

Abstract: BackgroundSerum bilirubin may have potent antioxidant and cytoprotective effects. Serum bilirubin levels are inversely associated with several cardiovascular and metabolic endpoints, but their association with nonalcoholic fatty liver disease (NAFLD) has not been investigated except for a single cross-sectional study in a pediatric population. We assessed the prospective association between serum bilirubin concentrations (total, direct, and indirect) and the risk for NAFLD.Methods and FindingsWe performed a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 53 publications
7
53
0
Order By: Relevance
“…Similar inverse relationship of NAFLD was discovered with conjugated and unconjugated bilirubin respectively [50,51] . In addition, serum bilirubin has been long recognised to have an inverse relationship with the development of coronary artery disease [52] .…”
Section: Anti-inflammatory and Anti-oxidantssupporting
confidence: 71%
“…Similar inverse relationship of NAFLD was discovered with conjugated and unconjugated bilirubin respectively [50,51] . In addition, serum bilirubin has been long recognised to have an inverse relationship with the development of coronary artery disease [52] .…”
Section: Anti-inflammatory and Anti-oxidantssupporting
confidence: 71%
“…Lower serum bilirubin levels were also reported in patients with the metabolic syndrome, in which bilirubin negatively correlated with circulating insulin levels and visceral adipose tissue [11]. In a large prospective study (5,900 Korean men; followed up between 2002 and 2009) higher serum direct (conjugated) bilirubin levels were significantly associated with a lower risk of developing nonalcoholic fatty liver disease (NAFLD) [12]. Less than 1% of the participants in the study had diabetes.…”
Section: Fieldmentioning
confidence: 82%
“…Less than 1% of the participants in the study had diabetes. One of the limitations of this study [12] is that the diagnosis of NAFLD was based on ultrasound findings instead of the 'gold standard' liver biopsy. However, it is difficult to see how such a large study could cope with the logistics of liver biopsies let alone the ethical restrictions associated with such a procedure.…”
Section: Fieldmentioning
confidence: 98%
“…So far the literature had excluded bilirubin as a guiding test for NAFLD. However, a study by Chang et al [35] revealed that serum conjugated bilirubin levels were significantly associated with a lower incidence of NAFLD. Nevertheless, some authors found that total bilirubin levels are associated in a negative way [36], and still others observed that unconjugated bilirubin levels are rigorously related to NAFLD [37,38], therefore, it is not clear which bilirubin influences NAFLD presence.…”
Section: Research Papermentioning
confidence: 97%